« À la nouvelle du désastre… » : rumeurs et sociabilité ordinaire en temps de crise (Flaubert, Zola) - Bertrand Marquer (Flaubert: Revue Critique et Génétique)
This article analyses the functioning of rumour in two “political” novels by Flaubert and Zola, L’Éducationsentimentale and La Fortune des Rougon, with a detour through the archaeological novel Salammbô. The aim is to show that the two novelists make rumour an element of ordinary sociability, whereas the context of these works would rather suggest that it is a symptom of a crisis. This novelistic choice, which differs from contemporary theories of rumour (considered as a pathological phenomenon), is part of the satire, and reflects the evolution of a society now led by Opinion.